Gastrointestinal stromal tumors in children and young adults: a clinicopathologic and molecular genetic study of 22 Korean cases. Issue 10 (12th June 2013) - Kang, Guhyun; Park, Young Soo; Jung, Eun‐Sun; Joo, Mee; Kang, Mi Seon; Ahn, Soomin; Kang, Gu Hyum; Kim, Kyoung‐Mee
<x xml:space="preserve">Abstract</x> Studies on gastrointestinal stromal tumors (GISTs) in young patients are limited due to their rarity, and none have been conducted in Asian populations. GISTs from patients under the age of 30 were retrospectively reviewed and were analyzed for clinicopathologic features, immunohistochemistry for SDHB (succinate dehydrogenase subunit B), and mutations for exon 9, 11, 13, and 17 of KIT gene and exon 12, 14, and 18 of PDGFRA gene. We found two pediatric (<18 years old) and 20 young adult (18–30 years old) GIST cases. Pediatric GISTs occurred in two girls, both as solitary masses with epithelioid histology in the stomach. Both GISTs were wild type for KIT and PDGFRA genes, were negative for SDHB, and there was no recurrence during follow‐up. Of the 20 GISTs in young adults, 12 (60%) were from extra‐gastric locations (six duodenum, five jejunum, and one esophagus), and 16 (80%) showed a spindle cell morphology. Mutations of KIT or PDGFRA genes were identified in 14 (78%) of the 18 cases. One patient with multiple gastric GISTs with perigastric lymph node metastases at presentation developed multiple distant metastases and died of the disease 7.3 years after diagnosis. Of the 19 R0‐resected young adult patients, one patient with small intestinal GIST harboring KIT exon 11 deletion mutation developed recurrence and showed partial responses for imatinib. In summary, compared with pediatric GIST cases, young adult GISTs are heterogeneous and share the characteristics of both pediatric and adult GISTs. When a mesenchymal tumor is clinically suspected in the small intestine of young adults, a GIST should be included in the differential diagnoses. Further mutation studies and extensive treatments are recommended for these cases.